The Sensible World and the World of Expression : Course Notes from the Collège de France, 1953 - Merleau-Ponty, Maurice, 1908-1961 (Book collections on Project MUSE., 2020)
"The Sensible World and the World of Expression presents the lecture notes for a course taught by Maurice Marleau-Ponty, a central figure of phenomenological philosophy, at a key point in his career"--